Drug-related problems and associated factors in Ethiopia: a systematic review and meta-analysis - Fuad Adem; Jemal Abdela; Dumessa Edessa; Bisrat Hagos; Abraham Nigussie; Mohammed A. Mohammed (Taylor & Francis Group, 2021)
Background Drug-related problems (DRPs) can occur at any stages of medication use processes, and a single drug could be associated with multiple DRPs. Once happened, it adversely affects health outcomes. In Ethiopia, evaluation of the magnitude and factors associated with DRPs had not been attempted at the national level. Method The literature search was conducted in the following databases; PubMed, Embase, Medline, and Google Scholar. The quality of the included studies was checked using Joanna Brigg's Institute (JBI's) checklist, and data were analyzed using Stata software (version 14.0). The pooled estimate of DRPs was computed by a Random effect model (DerSimonian-Laird method). Cochran's Q test (I2) statistic)), and Begg's correlation and Egger's regression test were assessed for heterogeneity and publication bias, respectively. Result Overall, 32 studies with a total sample size of 7,129 were included in the review. The estimated pooled prevalence of DRPs was 70% [0.70 (95% CI 0.64-0.76; I 2 = 97.6% p = 0.000)]. Polypharmacy (taking ≥ 5 drugs) [RR = 1.3], medical comorbidity [RR = 1.3], poor medication adherence [RR = 1.7], uncontrolled blood pressure [RR = 1.4], substance use [RR = 1.2], type 2 diabetes [RR = 1.8], significant drug interaction [RR = 1.33], and a negative medication belief [RR = 3.72] significantly influenced the occurrence of DRPs. Conclusion The estimated national prevalence of DRPs in Ethiopia was high. Presence of medical comorbidity, using multiple drugs, significant drug interaction, poor medication adherence, uncontrolled blood pressure, type 2 diabetes, substance use and a negative belief about medication significantly influenced the occurrence of DRPs. Initiating and/or strengthening pharmaceutical care services at the health care facilities could lower the occurrence of DRPs. PROSPERO registration number CRD42020162329.